2016
DOI: 10.1177/2325967116671501
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Arthroplasty Outcomes in Patients With Multiple Reported Drug Allergies

Abstract: Background:The presence of multiple allergies has been correlated with worse outcomes for patients undergoing hip and knee arthroplasty, but the effect of allergies has not yet been elucidated with respect to shoulder arthroplasty.Purpose/Hypothesis:The purpose of this study is to identify any discrepancies in shoulder arthroplasty outcomes with respect to reported drug allergies. We hypothesized that patients with multiple drug allergies would have inferior outcomes.Study Design:Cohort study; Level of evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Consistent with prior reports, our study did show that women more commonly had self-reported allergies than men. 11,15 On closer inspection of the published data, our inability to identify differences in foot and ankle outcomes based on PRAs may actually be more consistent with the commonly cited hip and knee arthroplasty studies on this topic. Comparing hip and knee arthroplasty patients without PRAs to patients with at least 1 PRA, Otero et al 12 12 To understand if the changes in MCS and PCS scores from Otero et al 12 were clinically relevant, we compared them to published data on the minimal clinically important difference (MCID) for the same outcome measures in hip arthroplasty patients.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Consistent with prior reports, our study did show that women more commonly had self-reported allergies than men. 11,15 On closer inspection of the published data, our inability to identify differences in foot and ankle outcomes based on PRAs may actually be more consistent with the commonly cited hip and knee arthroplasty studies on this topic. Comparing hip and knee arthroplasty patients without PRAs to patients with at least 1 PRA, Otero et al 12 12 To understand if the changes in MCS and PCS scores from Otero et al 12 were clinically relevant, we compared them to published data on the minimal clinically important difference (MCID) for the same outcome measures in hip arthroplasty patients.…”
Section: Discussionmentioning
confidence: 70%
“…Consistent with prior reports, our study did show that women more commonly had self-reported allergies than men. 11,15…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Rosenthal et al revealed that the presence of one or more self-reported allergies did not correlate with worse function, satisfaction, pain, or range of motion postoperatively. 4 On the contrary, another recent study demonstrated that a greater number of patient-reported allergies correlated with severe postoperative pain in patients undergoing elective total shoulder arthroplasty. 5 To date, there are very few studies in spine surgery that examine patient allergy lists, and their corresponding function and pain scores.…”
Section: Introductionmentioning
confidence: 96%